Spatially dependent modelling of pulsar wind nebula G0.9+0.1. Issue 3 (29th March 2018) - van Rensburg, C; Krüger, P P; Venter, C
Abstract: We present results from a leptonic emission code that models the spectral energy distribution of a pulsar wind nebula by solving a Fokker–Planck-type transport equation and calculating inverse Compton and synchrotron emissivities. We have created this time-dependent, multizone model to investigate changes in the particle spectrum as they traverse the pulsar wind nebula, by considering a time and spatially dependent B -field, spatially dependent bulk particle speed implying convection and adiabatic losses, diffusion, as well as radiative losses. Our code predicts the radiation spectrum at different positions in the nebula, yielding the surface brightness versus radius and the nebular size as function of energy. We compare our new model against more basic models using the observed spectrum of pulsar wind nebula G0.9+0.1, incorporating data from H.E.S.S. as well as radio and X-ray experiments. We show that simultaneously fitting the spectral energy distribution and the energy-dependent source size leads to more stringent constraints on several model parameters.